Optimal observational planning of local GPSnetworks: assessing an analytical method - Mehrabi H.; Voosoghi B. (Journal of Geodetic Science)
Precision, reliability and cost are the major criteriaapplied in optimization and design of geodetic networks.The terrestrial networks are being replaced quicklyby permanent and campaign Global Positioning System(GPS) networks. These networks must be optimized usingthe same three criteria. In this article the optimization ofthe observational plan of local GPS networks (Second OrderDesign (SOD)) is considered using the precision criterion.This study is limited to the selection of optimal numbersand the best distribution of the non-trivial baselinesthroughout the network. This objective is accomplishedbased on the SOD solution through the analytical methodin operational research by the means of quadratic programmingalgorithm. This presented method is tested ona real GPS network and appears to be a useful techniquein terms of cost reduction in the field work by the providedobservational plan and optimal distribution of thebaselines throughout the network. Results indicate thatweights of almost 36% of the baselines are negligiblewhencompared to the weights of the rest of the baselines; therefore,they could be eliminated fromthe observational plan,resulting in a 36% saving in the fieldwork cost.